Sistem Pendukung Keputusan Penerimaan Karyawan Dengan Metode Simple Additive Weighting (SAW) - Ismanto, Edi; Effendi, Noverta (SATIN - Sains dan Teknologi Informasi, 2017)
Universitas Muhammadiyah Riau is really need the support of technology information in order to facilitate its activities. AtÂ the time, there are usually find a case of an error of the recruitmentÂ process in an institution. It is also possible at Universitas Muhammadiyah Riau. It is actually depend on parties the agency that will make or break its own admission employes. Actually, the process of selecting the employee in accordance with the intelectual capability in quantity and the ability to work in accordance with its quality controlled. There are several criteria assessment in process of making decision recruitment at Universitas Muhammadiyah Riau. There assessment are based on the criteria of education, work experience, performance, test, interview, age, status, and address. The objectives to be achieved is to create a system that can help decision makers to determine the process recruitment optimally by using method of SAW (Simple Additive Weighting). The result of this research is building decision support system for acceptance new employes, and finally it can be uses as supporting for process accepting new employes.